The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmicb.2021.664833
|View full text |Cite
|
Sign up to set email alerts
|

E2 Site Mutations in S Protein Strongly Affect Hepatitis B Surface Antigen Detection in the Occult Hepatitis B Virus

Abstract: The mechanism of occult hepatitis B infection (OBI) has not yet been fully clarified. Our previous research found that novel OBI-related mutation within S protein, E2G, could cause the hepatitis B surface antigen (HBsAg) secretion impairment, which resulted in intracellular accumulation in OBI of genotype B. Here, to further explore the role of E2 site mutations in the occurrence of OBI, we analyzed these site mutations among 119 OBI strains identified from blood donors. Meanwhile, 109 wild-type HBV strains (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Furthermore, because the S gene’s open reading frame partially overlaps with that of the reverse transcriptase (RT) gene, mutations in the S gene cause antiviral resistance mutations to appear in the RT domain. The variation of S gene not only Strongly Affect HBsAg Detection ( Kuhns et al, 2021 ; Wang et al, 2021 ), but also leads to HBV drug resistance and immune escape ( Delfino et al, 2021 ). Drug resistance must be considered when a patient experiences a poor curative effect during a follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because the S gene’s open reading frame partially overlaps with that of the reverse transcriptase (RT) gene, mutations in the S gene cause antiviral resistance mutations to appear in the RT domain. The variation of S gene not only Strongly Affect HBsAg Detection ( Kuhns et al, 2021 ; Wang et al, 2021 ), but also leads to HBV drug resistance and immune escape ( Delfino et al, 2021 ). Drug resistance must be considered when a patient experiences a poor curative effect during a follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with OBI can be transmitted by blood transfusion and organ transplantation, including liver transplantation, and the clinical outcome of OBI is not known, and most of the results suggest that OBI is a significant risk factor for accelerated liver disease progression and the development of cirrhosis and hepatocellular carcinoma 31 .The www.nature.com/scientificreports/ molecular mechanism of OBI is not completely understood, and several possible mechanisms have been proposed, including mutations in the HBV gene resulting in undetectable HBsAg commercial assays; robust host suppression of HBV replication and transcription as well as immune surveillance; and coinfection with other viruses such as hepatitis C virus (HCV) 32,33 . Indeed, it has been reported that deletion of HBsAg in serum can be associated with mutations in the HBV-borne gene S [34][35][36] . Our preliminary study identified mutations in the S genes Q129R, T131N, M133S, F134L, and D144E in 7 serologically positive patients with MHD in combination with OBI, and no mutations in M133S have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one HBsAg-negative samples in the TMD region exhibited multiple amino acid substitution sites, many of which were newly discovered, such as E2K/R/D, G10D, A17R, F20L/S, L21V, L22V, F200Y, and S204N. E2 site mutations in the S protein are confirmed to impair secretion of HBsAg, which significantly affected detection of HBsAg ( 31 ). For genotype B, the highest mutation frequency of the S protein in HBsAg-negative patients was sF20L/S; regarding genotype C, sF19V/S had the highest frequency.…”
Section: Discussionmentioning
confidence: 99%